Myanmar Agricultural Performance Survey (Q1 2022): Farmgate prices and marketing by crop farmers - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
This Research Note presents the results from an assessment of output markets and crop prices in Myanmar after the monsoon of 2021. The results are based on data from a phone survey – the Myanmar Agriculture Performance Survey (MAPS) – that was conducted with almost 4,000 crop farmers in 281 townships in all states/regions of the country, over the period February 2022 – March 2022. We found that: Commercial rice income was down on average by 5 percent as farmers sold less of their harvest and stored more compared to the year before. Prices of crops linked to export markets increased more because of international price changes as well as the MMK depreciation than crops marketed domestically. For example, maize exported to Thailand increased by 53 percent and pigeon pea exported to India by 44 percent. There is strong heterogeneity in the evolution of income reported from crop sales. Compared to one year earlier, 35 percent of the farmers indicated an increase of crop sales income of more than 20 percent while 36 percent saw a decrease of more than 20 percent. Small farms in more insecure areas saw lower crop sales income increases compared to average farmers while farmers connected to export markets (maize and pulses) had relatively higher income increases from crop sales.